1997
DOI: 10.1063/1.363927
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen modification of hydrogenated amorphous carbon films

Abstract: The effect of nitrogen addition on the structural and electronic properties of hydrogenated amorphous carbon ͑a-C:H͒ films has been characterized in terms of its composition, sp 3 bonding fraction, infrared and Raman spectra, optical band gap, conductivity, and paramagnetic defect. The variation of conductivity with nitrogen content suggests that N acts as a weak donor, with the conductivity first decreasing and then increasing as the Fermi level moves up in the band gap. Compensated behavior is found at about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
136
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 342 publications
(148 citation statements)
references
References 40 publications
(51 reference statements)
10
136
1
1
Order By: Relevance
“…[4,17] It can be seen from Fig. 3 (a) that E th drops with addition of N similar to that reported elsewhere [4,16] but in contrast to the DLC films of Silva et al, [18] no reduction in N s is observed (Fig 3 (b)). The reduction in N s in the DLC films was attributed to the passivation of defects as evidenced by the initial increase in the Tauc gap followed by a subsequent decrease.…”
Section: (A)supporting
confidence: 86%
“…[4,17] It can be seen from Fig. 3 (a) that E th drops with addition of N similar to that reported elsewhere [4,16] but in contrast to the DLC films of Silva et al, [18] no reduction in N s is observed (Fig 3 (b)). The reduction in N s in the DLC films was attributed to the passivation of defects as evidenced by the initial increase in the Tauc gap followed by a subsequent decrease.…”
Section: (A)supporting
confidence: 86%
“…15,16 A hydrocarbon containing gas mixture of CH 4 /He/N 2 was dissociated at a rf power of 30 W to deposit a-C:H:N films on highly doped ͑0.01-0.001 ⍀ cm͒ n-Si substrates. The films were deposited on substrates held at room temperature, and the properties of the films can be found in the literature.…”
mentioning
confidence: 99%
“…The films were deposited on substrates held at room temperature, and the properties of the films can be found in the literature. 16 Nitrogen in amorphous carbon films is shown to act at a weak donor and alters the joint density of states in the films. Field-emission measurements were carried out using a parallel plate configuration with the film being the cathode and an ITO coated glass the anode placed 50 m from the cathode using glass fiber spacers.…”
mentioning
confidence: 99%
See 2 more Smart Citations